The Medicinal Fungus Cordyceps militaris: Academia to Industry in Thailand - Tapingkae, Tanya; Yachai, Mongkol; Tapingkae, Wanaporn (Journal of Nepal Biotechnology Association, 2024)
The medicinal mushroom (Cordyceps species) is a highly valued source of useful natural products having diverse biological activities. Cordyceps militaris (commonly known as orange caterpillar fungus), a kind of herbal drug and food additive mushroom, were used as a tonic food in Asia from ancient times. Their products have been developed from cultivated fruit bodies and fermented mycelia of C. militaris. Various studies of culture techniques will be expected to reduce contamination. A traditional methodology (autoclave) to sterilize culture media was compared with a protocol that included hydrogen peroxide to sterilize culture media (without autoclaving and inoculating cultures without the laminar airflow cabinet) for growing C. militaris CMRU strain. The results showed that the two methods had no significant differences in cordycepin production and biomass production. Production of C. militaris products is now becoming a large industry in Thailand.